Governance Capability Gap Analysis of SIMLITABMAS: A COBIT 2019-Based Evaluation Methodology and Literature Review - Fina Amru Millati; Basuki Rahmat; Faisal Muttaqin (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2025)
This study aims to evaluate and enhance the Information Technology (IT) governance capability of the SIMLITABMAS system using the COBIT 2019 framework. By integrating a literature study with a formal evaluation methodology, the research focuses its analysis on the Deliver, Service, and Support (DSS) domain, specifically DSS02 (Managed Service Requests and Incidents), DSS03 (Managed Problems), and DSS05 (Managed Security Services). Literature review results indicate that the DSS domain is a critical juncture in university digital services, which frequently encounters obstacles due to manual procedures. Capability measurement results reveal that SIMLITABMAS is currently at Level 3 (Defined) with a fulfillment rate of 75.2%. This finding confirms a one-level gap toward the target of Level 4 (Measured), driven by a high dependency on informal communication channels such as WhatsApp and low digital literacy among users regarding system manuals. As a strategic solution to bridge this gap, this study recommends the implementation of AI Chatbot technology as a 24/7 automated helpdesk. The integration of the COBIT 2019 methodology with this automation solution is proven to transform service governance from an ad-hoc stage toward a more standardized, secure, and quantitatively measurable support system to sustainably support institutional research productivity.